Transforming Agrifood Systems in South Asia (TAFSSA) Newsletter #1 - Khan, Nur-A-Mahajabin (International Maize and Wheat Improvement Center, 2023)
TAFSSA aims to deliver a coordinated program of research and engagement across the food production–to–consumption continuum to support equitable access to sustainable healthy diets, improve farmer livelihoods and resilience, and conserve land, air and groundwater resources. TAFSSA currently collaborates with ten of CGIAR’s Initiatives and with aligned non-pooled projects developing knowledge products, capacity-sharing, and innovation use across CGIAR’s five Impact Areas. The TAFSSA newsletter provides news and highlights, and more information on TAFSSA knowledge products published in 2022 and 2023.